2004
DOI: 10.1038/nature02272
|View full text |Cite
|
Sign up to set email alerts
|

A newly discovered Roseobacter cluster in temperate and polar oceans

Abstract: Bacterioplankton phylotypes of alpha-Proteobacteria have been detected in various marine regions, but systematic biogeographical studies of their global distribution are missing. Alpha-Proteobacteria comprise one of the largest fractions of heterotrophic marine bacteria and include two clades, SAR11 and Roseobacter, which account for 26 and 16% of 16S ribosomal RNA gene clones retrieved from marine bacterioplankton. The SAR11 clade attracted much interest because related 16S rRNA gene clones were among the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
253
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(272 citation statements)
references
References 23 publications
18
253
1
Order By: Relevance
“…While the Roseobacter clade as such is also widespread, very little is known about its distribution at the species level. Selje et al (2004) found that a particular phylotype of the Roseobacter clade affiliated cluster was widely distributed in temperate and polar waters, but was not detected in the tropical and sub-tropical areas. The abundance of the Roseobacter clade affiliated cluster correlates positively with phaeopigments and chlorophyll (Giebel et al, 2011) indicating an algal association.…”
Section: Introductionmentioning
confidence: 99%
“…While the Roseobacter clade as such is also widespread, very little is known about its distribution at the species level. Selje et al (2004) found that a particular phylotype of the Roseobacter clade affiliated cluster was widely distributed in temperate and polar waters, but was not detected in the tropical and sub-tropical areas. The abundance of the Roseobacter clade affiliated cluster correlates positively with phaeopigments and chlorophyll (Giebel et al, 2011) indicating an algal association.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these data suggest that the unique winter clones in clusters J, H and K may represent roseobacters adapted to the winter cold environment in a temperate estuary. Several distinct Roseobacter clusters have been identified in temperate and polar regions based on the 16S rRNA gene marker (Selje et al, 2004;Prabagaran et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Isolation and molecular ecology studies have revealed that the Roseobacter clade occupies diverse marine environments but is most predominant in coastal waters (Buchan et al, 2005). Furthermore, many roseobacters have been found in association with algal blooms (González et al, 2000;Alavi et al, 2001;West et al, 2008), and some roseobacters have been isolated from, and found to be dominant in polar environments (Brown and Bowman, 2001;Brinkmeyer et al, 2003;Selje et al, 2004;Prabagaran et al, 2007). The first complete genome sequence of a marine roseobacter, Silicibacter pomeroyi, was reported by Moran et al (2004), and there are now complete or draft genome sequences for ca.…”
Section: Introductionmentioning
confidence: 99%
“…Ely et al 2005;Goetze 2005 and 15 references therein) and this aspect of ocean evolution thus represents a 'serious challenge' to the idea of allopatric speciation (Palumbi 1994;see also Goetze 2005), which is often considered the predominant mode of speciation in terrestrial organisms (Mayr 1954(Mayr , 1963Winston 1999, p. 48;see Schilthuizen 2001, p. 186). However, advances in our understanding of oceanography and marine molecular ecology are increasingly revealing that the ocean is more physically heterogeneous than we thought, with shorter dispersal, smaller geographical ranges, smaller population sizes and lower gene flow (Rosenblatt 1963;Field et al 1997;Longhurst 1998;Jones et al 1999;Darling et al 2000;Carr et al 2003;Selje et al 2004;Goetze 2005). It is now clear that geographical speciation-including allopatric, parapatric and/or peripatric speciation-is common also in marine taxa (e.g.…”
Section: Introductionmentioning
confidence: 99%